THE INFLUENCE OF TRANSFORMATIONAL LEADERSHIP, WORK STRESS ON PERFORMANCE - Irsan Komar, Ida Aju Brahmasari, Riyadi Nugroho (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
This study aims to determine the effect of transformational leadership, work stress on employee performance at the Directorate General of Customs and Excise, East Java Regional Office I. The study population was 1323 employees. employees, the number of samples is 250 respondents. The technique of collecting data through a questionnaire. Model testing with structural equation modeling (SEM) analysis. The test results show that the model (fit) can be seen from the values ??of GFI, AGFI, TLI, CFI, RMSEA and CMIN / DF respectively 0.909, 0.901, 0.961, 0.965, 0.025 and 1.138 which indicate the model fit criteria. The results showed that: 1) Transformational Leadership has a significant effect on Work Stress, 2) Transformational Leadership has a significant effect on Performance, 3) Work Stress has a significant effect on Performance, 4) Transformational Leadership has no significant effect on Performance through Work Stress for employees at the Regional Office of the Directorate General. East Java Customs and Excise I.